1935 Wash. Sess. Laws 599-601, ch. 172, §§ 5-7 - (:unkn) unknown (My University, 1935)
No person shall carry a pistol in any vehicle or conceal on or about his person, except in his place of abode or fixed place of business, without a license therefor as hereinafter provided.
Keywords: CARRY